Quantifying tensile force and ERK phosphorylation on actin stress fibers - Hirata, Hiroaki; Gupta, Mukund; Vedula, Sri Ram Krishna; Lim, Chwee Teck; Ladoux, Benoît; Sokabe, Masahiro (Humana Press Inc., 2017)
ERK associates with the actin cytoskeleton, and the actin-associated pool of ERK can be activated (phosphorylated in the activation loop) to induce specific cell responses. Increasing evidence has shown that mechanical conditions of cells significantly affect ERK activation. In particular, tension developed in the actin cytoskeleton has been implicated as a critical mechanism driving ERK signaling. However, a quantitative study of the relationship between actin tension and ERK phosphorylation is missing. In this chapter, we describe our novel methods to quantify tensile force and ERK phosphorylation on individual actin stress fibers. These methods have enabled us to show that ERK is activated on stress fibers in a tensile force-dependent manner.
CRIS-Team Scopus Importer:2024-02-19
Keywords: Actomyosin; Contractility; MAP kinase; Mechanical stretch; Mechanotransduction; Micropillar; Tension